Effects of Dimethyl Anthranilate-Based Repellents on Behavior, Plumage Condition, Egg Quality, and Performance in Laying Hens - Terčič, Dušan; Pančur, Mojca; Jordan, Dušanka; Zupan Šemrov, Manja (Frontiers in Veterinary Science, 2020)
Feather pecking is a behavior that occurs in order to cope with a constrained environment and is a serious problem in the egg production industry. This longitudinal study was conducted under commercial conditions to investigate whether the application of two repellent mixtures, previously suggested as aversive to wild birds, to the plumage of Prelux-R hybrid egg layers is a viable alternative to beak trimming as a solution to discourage feather pecking among laying hens. A total of 180 untrimmed hybrid layers was reared together in a floor pen. At 18 weeks of age they were allocated randomly to three treatments (repellent P, repellent T, control), each consisting of 6 replicated enriched cages with 10 hens in each cage. Hens were evenly sprayed once every two weeks for 54 weeks with solution P (dimethyl anthranilate and methyl phenylacetate), solution T (dimethyl anthranilate and geraniol), or distilled water (control). Body weight, plumage condition, behavior, feed intake, and egg quality measurements were taken at five time periods from 26 to 76 weeks of age. Egg production and mortality were recorded daily. The treatments did not affect feather pecking behavior. Hens treated with repellent T tended to perform less cage pecking than the control hens. The use of the repellents did not reduce feather pecking, the plumage was even more significantly damaged in the hens given the repellents compared to the control hens. This suggests the chemicals in the repellents worsened the plumage. No differences in feed intake and daily egg production between treatments were found. Raw and hard-boiled eggs were highly uniform in odor/flavor/taste and no offensive odor absorption related to the chemicals in the repellents was detected. In conclusion, in the present study we did not find any beneficial effect of dimethyl anthranilate-based repellents on feather pecking frequency and plumage/feather condition. Therefore, we do not encourage their use in wider commercial settings.